COLLABORATION BETWEEN STATE AND NON-STATE ORGANIZATIONS IN THE PROCESS OF LEGAL SOCIALIZATION OF THE INDIVIDUAL (TAMADDUN NURI JURNALI, 2025)
This article provides an in-depth analysis of the collaboration between state and non-state organizations in the process of an individual's legal socialization. It examines the role of these institutions in shaping legal consciousness and legal culture, explores forms of cooperation, and discusses ways to enhance their effectiveness.